A detailed analysis of partial molecular volumes in DPPC/cholesterol binary bilayers - Miyoshi, Tsubasa; Lönnfors, Max; Peter Slotte, J.; Kato, Satoru (Biochimica et biophysica acta, 2014)
We examined the volumetric behavior of the dipalmitoylphosphatidylcholine (DPPC)/cholesterol binary bilayer system with high accuracy and more cholesterol concentrations to reveal the detailed molecular states in the liquid-disordered (Ld) phase, the liquid-ordered (Lo) phase and the gel phase. We measured the average specific volume of the binary bilayer at several temperatures by the neutral flotation method and calculated the average volume per molecule to estimate the partial molecular volumes of DPPC and cholesterol in each phase. As a result, we found that the region with intermediate cholesterol concentrations showed a more complicated behavior than expected from simple coexistence of Ld and Lo domains. We also measured fluorescence decay of trans-parinaric acid (tPA) added into the binary bilayer with more cholesterol concentrations to get further insight into the cholesterol-induced formation of the Lo phase. On the basis of these results we discuss the molecular interaction between DPPC and cholesterol molecule in the Lo phase and the manner of Ld/Lo phase coexistence. [Display omitted] •Bilayer density was measured with more cholesterol concentrations.•We obtained precise partial molecular volumes in the DPPC/cholesterol bilayer system.•Experiments with a fluorescent probe were consistent with the density measurements.•Our results provide new insight into Ld/Lo phase coexistence properties.